The challenge of multiple chronic comorbidities in family medicine (Portuguese Journal of Family Medicine and General Practice, 2008)
One of the challenges of family medicine is the need to assist patients with polipathology. The functional and pain limitations due to rheumatologic diseases claim for a good health care articulation. The family doctor is the one who better frames the patients biopsicosocial context and has an essential role in this integration. Its described a 49 year-old woman, retired for invalidity at 46 years, ex-seller promoter, natural from Matosinhos and living in Rio Tinto. Part of a nuclear family with 3 children, Duvall stadium VI, Graffar IV, family apgar 10 and a medium Segovia-Dreyer family risk. It´s presented her genogram, Thrower circle and family lifeline. She had been followed in rheumatology consultations for about 4 years, after the rheumatoid arthritis diagnosis in 1993 and developed diabetes, as a complication of chronic corticotherapy. For 4 years she cared for her semi-bedfast mother and, during this time, she was submitted to 4 orthopedic surgeries with an important functional limitation. Some months after her mothers death and her sons diagnosis of diabetes, she developed acute pancreatitis with septic shock. Since then she suffered several ostheoarticular infections, while watching some degradation of the family relationships. She has been keeping chronic resistant pain and a significant limitation (Karnovsky indice 40-50%). Three neighbours that the patient considers as family have assumed the main caretakers role. This case reveals a patient with multiple morbidities whose follow-up has been discontinued, suggesting a deficient articulation of primary and secondary care. Not dissociated from her chronic pain and marked functional limitation, there were several life events and family disequilibrium periods. With the present case we show the importance of implementing a patient-centered healthcare model that integrates the whole constellation of their comorbidities.
Keywords: Rheumatoid Arthritis; Polipathology; Comorbidity